2016
DOI: 10.1097/nmd.0000000000000416
|View full text |Cite
|
Sign up to set email alerts
|

Is Helplessness Still Helpful in Diagnosing Posttraumatic Stress Disorder?

Abstract: Criteria A2, experience of helplessness, fear, or horror at the time of the traumatic event, was removed from the posttraumatic stress disorder diagnosis in the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition. We argue that there is empirical support for retention of A2, a criterion that has clinical value and may improve diagnostic accuracy. Specifically, we demonstrate that A2 has high negative predictive power, aids in the prediction of symptom severity, and can be indispensible to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…= 9.6). This was done using DSM-IV criteria A1 (qualifying traumatic event) and A2 (experience of intense fear, helplessness, and horror in response to a criteria A1 traumatic event), which is predictive of PTSD symptom severity and has significant negative predictive power for PTSD diagnosis (for a recent reviw, see Pivovarova et al 2016).…”
Section: Participantsmentioning
confidence: 99%
“…= 9.6). This was done using DSM-IV criteria A1 (qualifying traumatic event) and A2 (experience of intense fear, helplessness, and horror in response to a criteria A1 traumatic event), which is predictive of PTSD symptom severity and has significant negative predictive power for PTSD diagnosis (for a recent reviw, see Pivovarova et al 2016).…”
Section: Participantsmentioning
confidence: 99%
“…Although helplessness is one of the A2 criteria for traumatic events dropped from DSM-5 for being thought to lead to false negatives (i.e. for various reasons, people may not always remember the exact nature of their peritraumatic reactions) (Pivovarova et al, 2016), we demonstrated that this specific emotional state might have a unique ability to predict greater hoarding in the context of an ongoing pandemic. Perhaps hoarding-related behaviors are a method of exerting control in a situation where individuals perceive they are devoid of control.…”
Section: Discussionmentioning
confidence: 76%
“…In clinical work, particularly with veterans, it is common to hear that the most thrilling event of their lives was successfully escaping from an ambush echoing the commonly accepted psychological notion that active avoidance of punishment is reinforcing. This may not be the case for predisposed people, which could diminish their avoidance of stressful situations with heightened potential for trauma exposure to the point of helplessness, which is an essential precursor for the development of PTSD (Pivovarova et al, 2016). This causality is far from been settled, however, with consistently documented counterfactual thoughts (Erwin et al, 2018;Kelley et al, 2019) and ruminations (Blix et al, 2018;Scott et al, 2018) regarding the index trauma as features of PTSD.…”
Section: Caveatsmentioning
confidence: 99%
“…There are noteworthy changes from DSM-IV TR to DSM 5 PTSD diagnostic criteria including, but not limited to the expansion of the type of incorporated symptomatology and to the deletion of a seemingly "indispensable" (Pivovarova et al, 2016) "fear, helplessness or horror" trauma response criterion (Pai et al, 2017). Consequently, in comparison to DSM-5, DSM-IV TR PTSD criteria yield a greater diagnostic sensitivity viz., fewer false negatives' rates (Schaal et al, 2015;Schnyder et al, 2015).…”
Section: Caveatsmentioning
confidence: 99%